The Effect of Subtitution Rice Bran Flour to The Physical, Chemical, Organoleptic, and Dietary Fiber of Goldband Catfish Meatballs (Clarias batrachus) - Hefti Salis Yufidasari; Eko Waluyo; Erlinda Indrayani; Rilo Akbar Viranto (Universitas Airlangga, 2020)
Meatballs are one of the most popular products of consumers. Starting from children to adults and even parents. Generally meatballs have a delicious, highly nutritious taste, can be eaten with and under any conditions and are easily accepted by consumers. Meatball products that are widely circulated in the market have a dietary fiber content (dietary fiber) as much as 0.5% of adult fiber needs or about 0.125 g - 0.15 g. The recommended standard for dietary fiber is 25-30 g / day. So it is necessary to add ingredients to increase the value of food fiber on meatball products. Materials that can be used in making meatballs to increase dietary fiber are bran flour, this is because rice bran is rich in dietary fiber, protein and minerals. Several studies on bran functionalities for health include obesity, diabetes, anti-cancer, and hypocholesterolemia. Rice bran has solulable dietary fiber content of 2.06% and insolulable dietary fiber 15.83%. The purpose of this study is to make fishery processed products that have added value as functional food in increasing dietary fiber and to get the best concentration on the physical, chemical and organoleptic properties of tilapia fish meatballs. The method used in this research is experiment. The experimental design in the main study was a simple Completely Randomized Design using 4 treatments and 5 replications. The independent variable used in this study was the difference in the concentration of bran flour 0%, 25%, 30% and 35% in tilapia meatballs. While the dependent variables in this study are physical properties (whiteness, lightness, hardness and springness), chemistry (protein, water, fat, ash and carbohydrates), dietary fiber and organoleptics (appearance, aroma, taste and texture) of tilapia meatballs. Data obtained from the study were then analyzed using SPSS version 25 software with Analysis of Variant ANOVA to determine the effect of treatment on several test parameters. These results were then followed by Tukey's further test. If the results show p <0.05, the treatment is significantly different. Furthermore, the best treatment of all treatments was carried out using the de Garmo method. The results showed that the addition of rice bran flour to tilapia meatballs had a significant effect on the characteristics of physics (whiteness, lightness, elasticity and hardness), chemical characteristics (water content, protein, fat, ash and carbohydrates), dietary fiber content and hedonic organoleptic characteristics appearance and texture, while the characteristics of hedonic organoleptic scents were not significantly different. Tilapia meatballs with the best bran flour substitution with de Garmo test were obtained in treatment 3 with bran concentrations of 30% with chemical test values namely water content 66.1%, protein content 10.8%, fat content 0.78%, content abu 1.98% carbohydrate content 20.33% and food fiber content 8.83%. Physical tests were whiteness 59.34, lightness 48.89, elasticity 0.88 and hardness 43.12 N. The hedonic organoleptic test texture was 2.76, flavor 2.7, aroma 3 and appearance 3.38. The best treatment parameters for tilapia meatballs are in accordance with Indonesia National Standart for fish meatballs, except for the parameters of water content.